On the interaction between landownership and regional designs for land development. (August 2015) - van Dijk, Terry; van der Vlist, Arno
This paper examines how landownership patterns are, partially, both a result of and a condition for the designs that planners make for sites. Designs emerge in the process of arriving at a development plan, preceding formal plans and decisions. We claim that during that process, landownership and designs are responsive to each other. To explore this interaction, we analysed two large development projects in the Netherlands. These two projects involve regional designs followed by anticipatory land acquisition by private and public agents. For these projects we reconstructed a timeline for the designing process that we positioned parallel to the changes in landownership. The result shows that the governments that took the lead in the projects added more detail to the plans only after they secured their active role for themselves by acquiring a dominant ownership position on sites eventually meant for housing. This analysis prompts an ethical discussion on government's double role in active land policy.